The Analysis of Language Style Found in “Clouds” Movie - Desak Putu Ananda Cintya Dewi; Anak Agung Gede Suarjaya; Made Sani Damayanthi Muliawan (CV. Tirta Pustaka Press, 2023)
This research entitled The Analysis of Language Style Found in Clouds Movie. in this research, the discussion is focused on language style and the factor that influences the use of language style found in Clouds Movie. This research aimed to find the types of language style and the factor in Clouds Movie. Furthermore, this research used qualitative descriptive method. It was done by applying some steps. First, the data was downloaded from website browser movie subtitle entitled “Clouds”. After that, the movie was watched and then made the transcript. The next step, understanding the conversation of each character to find out the type of language style and the factor that influence the language style in the movie. The last step was collecting all the data and analyze it based on the theories. The theories applied in this paper were the theory of language style by Martin Joos and the theory of factor by Holmes. The result shows there are three language style used in it, namely casual style, consultative style, and intimate style. In addition, the factor that influences the use of language style in Clouds Movie, were participants, topic, setting, and function.